Experiencia con la técnica Puzzle de Aronson para contenidos de cálculo diferencial (2017)
The classroom experience exposed in this paper aims to use the Aronson method as facilitator of the collaborative learning process of contents of a course of differential calculus, in particular the limits of a continuous function of , form, with students of the third semester of Mathematics from Universidad Pedagógica y Tecnológica de Colombia, in order to see another possibility of teaching and learning in the classroom at undergraduate levels.